2021
DOI: 10.1002/tal.1834
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐based seismic design of the outrigger of a high‐rise overrun building with asymmetric vertical setback in a strong earthquake area

Abstract: Summary Outriggers, which should be systematically analyzed and designed based on seismic performance methods in the different seismic level actions, can improve the lateral stiffness of irregular high‐rise structures. In this paper, a concrete‐filled steel frame‐core tube‐outrigger structural system is adopted for a practical overrun high‐rise building with an obviously asymmetrical vertical setback in a high‐intensity seismic region. To ensure the seismic safety of irregular high‐rise building structures, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…[24][25][26][27][28][29][30] Eom et al 7 in their paper suggested that observing the axial forces on the column above and below the outrigger helps in evaluating the force transmission in outriggers. Hoenderkamp 24 and Huang et al 31 suggested that analysis of the behavior of the outrigger floor slabs is frequently disregarded, and in their paper, they considered the slab behavioral analysis at outrigger level as it is through the slab the shear force from EQ is transferred. Thus, the influence of slab on the behavioral analysis of a HOS is a significant factor that needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30] Eom et al 7 in their paper suggested that observing the axial forces on the column above and below the outrigger helps in evaluating the force transmission in outriggers. Hoenderkamp 24 and Huang et al 31 suggested that analysis of the behavior of the outrigger floor slabs is frequently disregarded, and in their paper, they considered the slab behavioral analysis at outrigger level as it is through the slab the shear force from EQ is transferred. Thus, the influence of slab on the behavioral analysis of a HOS is a significant factor that needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the horizontal components (e.g., coupling beam and outrigger), highperformance energy dissipation components can be introduced to dissipate plastic energy, and reduce damage to the vertical components to ensure the seismic performance of the main structure (Yang et al, 2016;Ding et al, 2018). Frame-core tube-outrigger systems, which are typical hybrid lateral loadresisting systems, and have been widely used in modern super-tall buildings (Park and Oh, 2018;Zhang et al, 2018;Shim et al, 2019;Alhaddad et al, 2020;Huang et al, 2021). In this system, the outrigger is typically designed as an energy dissipation component that is elastic under the service level earthquake (SLE) and the design basis earthquake (DBE).…”
Section: Introductionmentioning
confidence: 99%